A meta-analytic review of the relationship between social constructs and athlete burnout - Pacewicz, C. E.; Mellano, K. T.; Smith, A. L. (Psychology of Sport and Exercise, 2019)
Objectives: Athlete burnout is a maladaptive sport experience characterized by emotional and physical exhaustion, perceptions of reduced accomplishment, and sport devaluation. Physical and psychosocial factors can initiate athlete burnout perceptions, making the social context of sport an important consideration when seeking to understand this experience. To advance understanding of the sport social context and athlete burnout perceptions, there is a need to inventory what social constructs have been examined and to assess their respective strengths of association with burnout perceptions. Accordingly, the purpose of this study was to systematically review and quantify the relationships between social constructs and athlete burnout perceptions. Design: Meta-analytic review. Method: A comprehensive search of athlete burnout literature from 2001 forward was conducted and meta-analytic procedures were applied to data from studies meeting inclusion criteria. Results: Twenty studies met the inclusion criteria, with three predominant social constructs represented (social support, n?=?8 studies; relatedness, n?=?10 studies; negative social interactions, n?=?3 studies). Meta-analysis using random effects models showed low-to-moderate inverse relationships of burnout dimensions with social support and relatedness and low-to-moderate positive relationships of burnout dimensions with negative social interactions. Conclusions: Positive aspects of the sport social context have potential to mitigate athlete burnout perceptions. However, only two positive social constructs are prevalently studied. A broader span of social constructs should be included in quantitative athlete burnout research, particularly those capturing negative aspects of the sport social context, to better understand social contributors to athlete burnout perceptions.